Effects of Simvastatin and Metformin on Polycystic Ovary Syndrome after Six Months of Treatment - Banaszewska, Beata (Endocrine Society, 2011)
CONTEXT: A randomized trial on women with polycystic ovary syndrome (PCOS) compared simvastatin, metformin, and a combination of these drugs. OBJECTIVE: The aim of the study was to evaluate long-term effects of simvastatin and metformin on PCOS. DESIGN: Women with PCOS (n = 139) were randomized to simvastatin (S), metformin (M), or simvastatin plus metformin (SM) groups. Evaluations were performed at baseline and at 3 and 6 months. SETTING: The study was conducted at a university medical center. PRIMARY OUTCOME: We measured the change of serum total testosterone. RESULTS: Ninety-seven subjects completed the study. Total testosterone decreased significantly and comparably in all groups: by 25.6, 25.6, and 20.1% in the S, M, and SM groups, respectively. Both simvastatin and metformin improved menstrual cyclicity and decreased hirsutism, acne, ovarian volume, body mass index, C-reactive protein, and soluble vascular cell adhesion molecule-1. Dehydroepiandrosterone sulfate declined significantly only in the S group. Total cholesterol and low-density lipoprotein cholesterol significantly declined only in the S and SM groups. Ongoing reduction of ovarian volume, decreased hirsutism, acne and testosterone were observed between 0 and 3 months as well as between 3 and 6 months. Improvement of lipid profile, C-reactive protein, and soluble vascular cell adhesion molecule-1 occurred only during the first 3 months of treatment, with little change thereafter. Treatments were well tolerated, and no significant adverse effects were encountered. CONCLUSIONS: Long-term treatment with simvastatin was superior to metformin. Improvement of ovarian hyperandrogenism continued throughout the duration of the study.